Expand menu menu_open Minimize Go to startpage home Home History history History expand_more
{{ item.displayTitle }}
navigate_next
No history yet!
Progress & Statistics equalizer Progress expand_more
Student
navigate_next
Teacher
navigate_next
{{ filterOption.label }}
{{ item.displayTitle }}
{{ item.subject.displayTitle }}
arrow_forward
No results
{{ searchError }}
search
menu
{{ courseTrack.displayTitle }} {{ printedBook.courseTrack.name }} {{ printedBook.name }}
{{ statistics.percent }}% Sign in to view progress
search Use offline Tools apps
Digital tools Graphing calculator Geometry 3D Graphing calculator Geogebra Classic Mathleaks Calculator Codewindow
Course & Book Compare textbook Studymode Stop studymode Print course
Tutorials Video tutorials Formulary

Video tutorials

How Mathleaks works

Mathleaks Courses

How Mathleaks works

play_circle_outline
Study with a textbook

Mathleaks Courses

How to connect a textbook

play_circle_outline

Mathleaks Courses

Find textbook solutions in the app

play_circle_outline
Tools for students & teachers

Mathleaks Courses

Share statistics with a teacher

play_circle_outline

Mathleaks Courses

How to create and administrate classes

play_circle_outline

Mathleaks Courses

How to print out course materials

play_circle_outline

Formulary

Formulary for text courses looks_one

Course 1

looks_two

Course 2

looks_3

Course 3

looks_4

Course 4

looks_5

Course 5

Login account_circle menu_open

Solving Rational Equations

Equations with rational expressions are called rational equations. Like all equations, these can be solved graphically and algebraically. Sometimes, when solving algebraically, extraneous solutions — or solutions that do not satisfy the equation — arise.
Method

Solving Rational Equations Graphically

A rational function is a function that contains at least one rational expression, such as y=4xx+52x. y=\dfrac{4x}{x+5}-\dfrac{2}{x}. If the dependent variable of the function is exchanged for a constant, say C,C, the result is a rational equation, C=4xx+52x, C=\dfrac{4x}{x+5}-\dfrac{2}{x},

which can be solved graphically. This is done by first graphing the function y=4xx+52x,y=\frac{4x}{x+5}-\frac{2}{x}, then finding the yy-coordinate(s) of the point(s) on the graph that has the yy-coordinate C.C. Then, the xx-coordinate(s) is the solution to the equation.
Exercise

Solve the rational equation graphically. 1x+2+2=3 \dfrac{1}{x+2}+2=3

Solution

When solving an equation graphically, we first rearrange the equation to get all variable-terms on one side and all constants on the other side. 1x+2+2=31x+2=1 \dfrac{1}{x+2}+2=3 \quad \Leftrightarrow \quad \dfrac{1}{x+2}=1 The left-hand side of the equation can now be expressed as a function, f(x)=1x+2,f(x)=\frac{1}{x+2}, which we graph in a coordinate plane.

The solution to the equation is the xx-value of the point where the function equals 1.1. We'll mark this point on the graph.

From the graph, we see that f(-1)=1.f(\text{-} 1)=1. This means the solution to the equation is x=-1.x=\text{-} 1. We can verify this by substituting it into the equation.
1x+2+2=3\dfrac{1}{x+2}+2=3
1-1+2+2=?3\dfrac{1}{{\color{#0000FF}{\text{-} 1}}+2}+2\stackrel{?}{=}3
11+2=?3\dfrac{1}{1}+2\stackrel{?}{=}3
1+2=?31+2\stackrel{?}{=}3
3=33=3
Since x=-1x=\text{-} 1 makes a true statement, it is a solution to the equation.
info Show solution Show solution
Method

Solving a Rational Equation by Multiplying Denominators

In rational equations, variable terms are in the denominator. To solve a rational equation, it is necessary to move the variables out of the denominator. Because the domain of rational functions is restricted, some solutions might be extraneous. Thus, it is necessary to verify the solutions. Consider the following equation as an example. 1x+1+1x1=-12x \dfrac{1}{x+1} + \dfrac{1}{x-1} = \text{-} \dfrac{1}{2x}

1

Multiply equation by denominators

To begin, it's necessary to get the variable terms out of the denominator(s). Here, xx is in the denominator of three different ratios. To get (x+1)(x+1) out of the denominator of the first ratio, multiply the equation by (x+1).(x+1). This yields (x+1)(1x+1+1x1)=(x+1)(-12x)x+1x+1+x+1x1=-x+12x1+x+1x1=-x+12x\begin{aligned} {\color{#0000FF}{(x+1)}} \left( \dfrac{1}{x+1} + \dfrac{1}{x-1}\right) &= {\color{#0000FF}{(x+1)}}\left(\text{-} \dfrac{1}{2x}\right) \\ \dfrac{{\color{#0000FF}{x+1}}}{x+1} + \dfrac{{\color{#0000FF}{x+1}}}{x-1} &= \text{-} \dfrac{{\color{#0000FF}{x+1}}}{2x}\\ 1 + \dfrac{x+1}{x-1} &= \text{-} \dfrac{x+1}{2x} \end{aligned} Notice that the variable term is no longer stuck in the denominator of the first ratio. The other denominators (x1)(x-1) and (2x)(2x) must be handled in the same way. This leads to multiplying the entire equation by (x+1),(x1)(x+1), (x-1) and (2x),(2x), which can be done in one step. Consider multiplying the first ratio by all three denominators. (x+1)(x1)(2x)1x+1 (x+1)(x-1)(2x)\cdot \dfrac{1}{x+1} (x+1)(x1)(2x)x+1 \dfrac{({\color{#0000FF}{x+1}})(x-1)(2x)}{{\color{#0000FF}{x+1}}} (x1)(2x) (x-1)(2x) As can be seen, the denominator of the ratio is eliminated and what remains is the product of the numerator and the other denominators. This will happen for each ratio in the equation. Now that the work has been explained, solving the equation can begin.

1x+1+1x1=-12x\dfrac{1}{x+1} + \dfrac{1}{x-1} = \text{-} \dfrac{1}{2x}
(x+1)(x1)(2x)(1x+1+1x1)=(x+1)(x1)(2x)(-12x){\color{#0000FF}{(x+1)(x-1)(2x)}} \left(\dfrac{1}{x+1} + \dfrac{1}{x-1}\right) = {\color{#0000FF}{(x+1)(x-1)(2x)}} \left( \text{-} \dfrac{1}{2x} \right)
(x+1)(x1)(2x)x+1+(x+1)(x1)(2x)x1=-(x+1)(x1)(2x)2x\dfrac{(x+1)(x-1)(2x)}{x+1} + \dfrac{(x+1)(x-1)(2x)}{x-1}=\text{-} \dfrac{(x+1)(x-1)(2x)}{2x}
(x+1)(x1)(2x)x+1+(x+1)(x1)(2x)x1=-(x+1)(x1)(2x)2x\dfrac{\cancel{(x+1)}(x-1)(2x)}{\cancel{x+1}} + \dfrac{(x+1)\cancel{(x-1)}(2x)}{\cancel{x-1}}=\text{-} \dfrac{(x+1)(x-1)\cancel{(2x)}}{\cancel{2x}}
(x1)(2x)+(x+1)(2x)=-(x+1)(x1)(x-1)(2x) + (x+1)(2x)=\text{-} (x+1)(x-1)

2

Consolidate variable terms
Notice that there are several terms that contain variables. In order to solve the equation, it is necessary to consolidate these terms. To do this, distribute and combine like terms.
(x1)(2x)+(x+1)(2x)=-(x+1)(x1)(x-1)(2x) + (x+1)(2x)=\text{-} (x+1)(x-1)
2x22x+2x2+2x=-(x2x+x1)2x^2-2x + 2x^2+2x = \text{-} (x^2-x+x-1)
4x2=-(x21)4x^2 = \text{-} (x^2-1)
4x2=-x2+14x^2= \text{-} x^2+1
5x2=15x^2=1

3

Solve the resulting equation

Now that the variable terms have been consolidated, the equation can be solved. Notice here that the resulting equation is quadratic. This will not always be the case. The type of equation determines which method to use. Here, square roots will be used.

5x2=15x^2=1
x2=15x^2=\dfrac{1}{5}
x2=0.2x^2=0.2
x=±0.2x=\pm \sqrt{0.2}
x=±0.44721x =\pm 0.44721 \ldots
x1=0.44721x2=-0.44721\begin{array}{l}x_1 = 0.44721 \ldots \\ \\ x_2 =\text{-} 0.44721 \ldots \end{array}

4

Check for extraneous solutions
The solutions found in Step 33 might be extraneous. Thus, they must be verified in the original equation. First, the solution x=0.44721x=0.44721 \ldots is tested.
1x+1+1x1=-12x\dfrac{1}{x+1} + \dfrac{1}{x-1} = \text{-} \dfrac{1}{2x}
10.44721+1+10.447211=?-12(0.44721)\dfrac{1}{{\color{#0000FF}{0.44721\ldots}}+1} + \dfrac{1}{{\color{#0000FF}{0.44721\ldots}}-1} \stackrel{?}{=} \text{-} \dfrac{1}{2\left({\color{#0000FF}{0.44721\ldots}}\right)}
0.69098+(-1.80900)=?1.118030.69098\ldots + (\text{-} 1.80900\ldots) \stackrel{?}{=} 1.11803\ldots
-1.11803=-1.11803\text{-} 1.11803\ldots = \text{-} 1.11803\ldots
The first value made a true statement. Thus, it is a solution to the equation. Next x=-0.44721x=\text{-} 0.44721\ldots is tested.
1x+1+1x1=-12x\dfrac{1}{x+1} + \dfrac{1}{x-1} = \text{-} \dfrac{1}{2x}
1-0.44721+1+1-0.447211=?-12(-0.44721)\dfrac{1}{{\color{#0000FF}{\text{-} 0.44721\ldots}}+1} + \dfrac{1}{{\color{#0000FF}{\text{-} 0.44721\ldots}}-1} \stackrel{?}{=} \text{-} \dfrac{1}{2\left({\color{#0000FF}{\text{-} 0.44721\ldots}}\right)}
1.80901+(-0.69098)=?1.118031.80901\ldots + (\text{-} 0.69098\ldots) \stackrel{?}{=} 1.11803\ldots
1.11803=1.118031.11803\ldots = 1.11803\ldots
This value also makes a true statement. Thus, it is also a solution.
Exercise

Tamara and Jamie are trimming the hedges in their front yard this weekend. Working together, this task takes 77 hours. If Tamara works alone, it will take her 1111 hours. How long would it take Jamie to trim the hedges on her own?

Solution
To begin, we can think of the time it takes for this task to be completed as a speed or rate expressed as a ratio. Since it takes Tamara 1111 hours to complete 11 task, we can express her rate as T=1 task11 hours=111task/hour T=\dfrac{1 \text { task}}{11 \text{ hours}} = \dfrac{1}{11} \text{task/hour} It can be seen that in 11 hour, Tamara will complete 111\frac{1}{11} of the work. A ratio to express Jamie's rate can be written in the same way. Since the number of hours it takes her to complete the task is unknown, we'll use x.x. J=1 taskx hours=1xtask/hour J=\dfrac{1 \text { task}}{x \text{ hours}} = \dfrac{1}{x} \text{task/hour} The time it takes for Tamara and Jamie to complete the task together is 77 hours. This ratio is 1 task7 hours.\frac{1 \text{ task}}{7 \text{ hours}}. Thus, the following rational equation can be written. 17=111+1x. \dfrac{1}{7} = \dfrac{1}{11} + \dfrac{1}{x}. Solving this equation will tell us how long it takes Jamie to trim the hedges on her own. To solve, we'll isolate the variable term, then use inverse operations. Remember, before combining fractions, they must have a common denominator.
17=111+1x\dfrac{1}{7} = \dfrac{1}{11} + \dfrac{1}{x}
17111=1x\dfrac{1}{7}-\dfrac{1}{11}=\dfrac{1}{x}
1177111=1x\dfrac{11}{77}-\dfrac{1}{11}=\dfrac{1}{x}
1177777=1x\dfrac{11}{77}-\dfrac{7}{77}=\dfrac{1}{x}
477=1x\dfrac{4}{77}=\dfrac{1}{x}
4x77=1\dfrac{4x}{77}=1
4x=774x=77
x=774x=\dfrac{77}{4}
x=19.25x=19.25
Thus, it will take Jamie 19.2519.25 hours or 1919 hours and 1515 minutes to trim the hedges on her own.
info Show solution Show solution
Concept

Inverse Functions to Rational Functions

A function is said to be invertible if each yy-value corresponds to exactly one xx-value. One way to determine if a function is invertible, is to draw its graph and perform the horizontal line test. The same holds true for rational function.
Exercise

Determine if f(x)=3x25f(x)=\frac{3}{x^2-5} is invertible. Then, find the inverse of f(x).f(x).

Solution

A function is invertible if its inverse is a function. One way to determine this is to perform the horizontal line test on the graph of the function.

We can move an imaginary horizontal line across the graph. If it intersects the graph at more than one point anywhere, the inverse is not a function. We'll draw an arbitrary horizontal line. Sometimes more than one must be drawn.

Since the line intersects the graph twice, the inverse is not a function. Thus, ff is not invertible. However, that doesn't stop us from finding the inverse of f(x).f(x). To do this, we can replace f(x)f(x) with yy in the function rule, then switch xx and y.y. y=3x25x=3y25 y=\dfrac{3}{x^2-5} \quad \Leftrightarrow \quad x=\dfrac{3}{y^2-5} We now solve this equation for y.y.
x=3y25x=\dfrac{3}{y^2-5}
(y25)x=3\left(y^2-5\right)x=3
y25=3xy^2-5=\dfrac{3}{x}
y2=3x+5y^2=\dfrac{3}{x}+5
y=±3x+5y=\pm \sqrt{\dfrac{3}{x}+5}
Thus, the inverse of f(x)f(x) is f-1=±3x+5. f^{\text{-} 1}=\pm \sqrt{\dfrac{3}{x}+5}.
info Show solution Show solution
{{ 'mldesktop-placeholder-grade-tab' | message }}
{{ 'mldesktop-placeholder-grade' | message }} {{ article.displayTitle }}!
{{ grade.displayTitle }}
{{ exercise.headTitle }}
{{ 'ml-tooltip-premium-exercise' | message }}
{{ 'ml-tooltip-programming-exercise' | message }} {{ 'course' | message }} {{ exercise.course }}
Test
{{ 'ml-heading-exercise' | message }} {{ focusmode.exercise.exerciseName }}
{{ 'ml-btn-previous-exercise' | message }} arrow_back {{ 'ml-btn-next-exercise' | message }} arrow_forward